RETRACTED: Modification of porous carbon-containing materials by silver nanoparticles - Aronbaev Dmitry; Isakova Dilnoza; Aronbaev Sergey; Abilkosimova Gulnoza (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001